Analyses of Mineral Content and Heavy Metal of Honey Samples from South and East Region of Turkey by Using ICP-MS - Serap Kılıç Altun; Hikmet Dinç; Nilgün Paksoy; Füsun Karaçal Temamoğulları; Mehmet Savrunlu (International Journal of Analytical Chemistry)
The substantial of mineral ingredients in honey may symbolize the existence of elements in the plants and soil of the vicinity wherein the honey was taken. The aim of this study was to detect the levels of 13 elements (Potassium (K), Sodium (Na), Calcium (Ca), Iron (Fe), Zinc (Zn), Cadmium (Cd), Copper (Cu), Manganese (Mn), Lead (Pb), Nickel (Ni), Chromium (Cr), Aluminum (Al), and Selenium (Se)) in unifloral and multifloral honey samples from south and east regions of Turkey. Survey of 71 honey samples from seven different herbal origins, picked up from the south and east region of Turkey, was carried out to determine their mineral contents during 2015-2016. The mineral contents were analyzed by inductively coupled plasma mass spectrometry (ICP-MS). The most abundant minerals were K, Na, and Ca ranging within 1.18–268 ppm, 0.57–13.1 ppm, and 0.77–4.5 ppm, respectively. Zn and Cu were the most abundant trace element while Pb, Cd, Ni, and Cr were the lowest heavy metals in the honey samples surveyed, with regard to the concentrations of heavy metals such as Zn, Cu, Pb, Cd, Ni, and Cr suggested and influence of the botanical origin of element composition. Geochemical and geographical differences are probably related to the variations of the chemical components of honey samples.